2011
DOI: 10.1186/1824-7288-37-27
|View full text |Cite
|
Sign up to set email alerts
|

The opinion of clinical staff regarding painfulness of procedures in pediatric hematology-oncology: an Italian survey

Abstract: BackgroundBeliefs of caregivers about patient's pain have been shown to influence assessment and treatment of children's pain, now considered an essential part of cancer treatment. Painful procedures in hematology-oncology are frequently referred by children as the most painful experiences during illness. Aim of this study was to evaluate professionals' beliefs about painfulness of invasive procedures repeatedly performed in Pediatric Hemato-Oncology Units.MethodsPhysicians, nurses, psychologists and directors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 35 publications
(26 reference statements)
0
15
0
Order By: Relevance
“…Children view lumbar punctures (LPs) as painful 1 and distressing. 2 Compared to adults, 3 subcutaneous lidocaine is underutilized in children, 4 despite evidence 5-8 and guidelines supporting its use. [9][10][11] Numerous studies demonstrate a suboptimal provision of analgesia in neonates and children undergoing LPs.…”
Section: Introductionmentioning
confidence: 99%
“…Children view lumbar punctures (LPs) as painful 1 and distressing. 2 Compared to adults, 3 subcutaneous lidocaine is underutilized in children, 4 despite evidence 5-8 and guidelines supporting its use. [9][10][11] Numerous studies demonstrate a suboptimal provision of analgesia in neonates and children undergoing LPs.…”
Section: Introductionmentioning
confidence: 99%
“…42 Thus, it is essential that healthcare workers realise their responsibilities and obligations for children's pain management. In our study, all of the paediatricians reported that there was no clinical training on pain management and nine (82%) suggested that formal training would be useful.…”
Section: Open Accessmentioning
confidence: 99%
“…Careful attention to the emotional outcomes of invasive procedures is often limited, and only 36% of Centers of Pediatric Oncology and Hematology in Italy reported that they ask children to give an assessment of the pain experienced following the procedure, and only 22% ask during the procedure …”
Section: Introductionmentioning
confidence: 99%
“…Careful attention to the emotional outcomes of invasive procedures is often limited, and only 36% of Centers of Pediatric Oncology and Hematology in Italy reported that they ask children to give an assessment of the pain experienced following the procedure, and only 22% ask during the procedure. 53 The eventual evaluation of pain control efficacy is assigned to either the operators themselves or the caregivers, 54,55 although the child's perception of the invasiveness of the procedure and the related painful experience has been confirmed to be poorly understood. [56][57][58][59][60][61] Therefore, we considered that involving children in decision-making about medical support during the procedure could mitigate some of their emotional distress.…”
mentioning
confidence: 99%